Cellular Functions of Optineurin in Health and Disease. Issue 9 (September 2016) - Slowicka, Karolina; Vereecke, Lars; van Loo, Geert
Abstract : Optineurin (OPTN) was initially identified as a regulator of NF-κB and interferon signaling, but attracted most attention because of its association with various human disorders such as glaucoma, Paget disease of bone, and amyotrophic lateral sclerosis. Importantly, OPTN has recently been identified as an autophagy receptor important for the autophagic removal of pathogens, damaged mitochondria, and protein aggregates. This activity is most likely compromised in patients carrying OPTN mutations, and contributes to the observed phenotypes. In this review we summarize recent studies describing the molecular mechanisms by which OPTN controls immunity and autophagy, and discuss these findings in the context of several diseases that have been associated with OPTN (mal)function. Trends: OPTN is necessary to mount antiviral IFN type I responses. Genetic ablation of OPTN or expression of an OPTN mutant defective in ubiquitin binding impairs TBK1 and IRF3 activation, and lowers levels of secreted IFN-β. Pathogen recognition and elimination through autophagy is mediated by the autophagy receptor OPTN and its upstream kinase TBK1. OPTN is a primary receptor required for the selective autophagy of damaged mitochondria. This process is also regulated via OPTN phosphorylation by TBK1. Through association with and subsequent ubiquitination by the E3 ligase HACE1, OPTN can bind to the autophagy receptor SQSTM1/p62 and regulate autophagy flux. This ubiquitination event also leads to the proteasomal degradation of OPTN. Mutations in the OPTN gene have been identified in patients suffering from Paget disease of bone and in neurodegenerative diseases including glaucoma, amyotrophic lateral sclerosis, and frontotemporal dementia.